The effect of bupivacaine on analgesia and safety in patients undergoing hemorrhoidectomy: a meta-analysis - Haixia Lu; Haixia Lu; Min Cai; Dongxi Zhou; Weiwei Li; Hanzhong Cao (Frontiers Media S.A., 2024)
Aim: There is no meta-analysis reporting the analgesic effect and safety of bupivacaine in patients undergoing hemorrhoidectomy. This meta-analysis provides quantitative evidence of the effect of bupivacaine in hemorrhoidectomy.Methods: Studies were searched from PubMed, Embase, the Cochrane Library, and the Web of Science. Standardized mean difference (SMD), weighted mean difference (WMD), and odds ratios (ORs) with 95% confidence interval (CI) were used as effect indicators. Heterogeneity was assessed using the I2 index, and sensitivity analysis was conducted to determine the effect of the single study on the pooled results.Results: A total of 18 studies were included in this meta-analysis. The pain level at 48 h was lower in the bupivacaine-combined other drug group than in the other drug group (WMD = −0.65, 95% CI: 1.18 to −0.11, and I2 = 37.50%). Compared to the bupivacaine group, the odds of pruritus (OR = 12.11, 95% CI: 1.49-98.59, and I2 = 0%) and urinary retention (OR = 4.45, 95% CI: 1.12-17.70, and I2 = 0%) were higher, and the pain level at 6 h (WMD = −2.13, 95% CI: 3.22 to −1.04, and I2 = 64.30%), at 12 h (WMD = −1.55, 95% CI: 2.19 to −0.90, and I2 = 56.10%), and at 24 h (SMD = −1.15, 95% CI: 1.89 to −0.42, and I2 = 82.5%) were lower in the bupivacaine-combined other drug group.Conclusion: Bupivacaine-combined other drugs had a good analgesic effect after hemorrhoidectomy, but the adverse reactions should be considered.